AGE-RELATED MACULAR DEGENERATION–ASSOCIATED PERIPAPILLARY CHOROIDAL NEOVASCULARIZATION IN THE ERA OF ANTI–VASCULAR ENDOTHELIAL GROWTH FACTOR THERAPY. Issue 10 (October 2019) - Lin, Tiezhu; Dans, Kunny; Meshi, Amit; Muftuoglu, Ilkay Kilic; Amador-Patarroyo, Manuel J.; Chen, Kevin C.; Cheng, Lingyun; Freeman, William R.
Abstract : Purpose: To characterize the natural history and response of age-related macular degeneration–associated peripapillary choroidal neovascularization to anti–vascular endothelial growth factor therapy. Methods: This was a retrospective case series of patients with peripapillary choroidal neovascularization secondary to neovascular age-related macular degeneration. All patients underwent complete ophthalmologic examination and retinal imaging including fluorescein angiography and spectral domain optical coherence tomography at each visit. Eyes with subretinal or intraretinal macular fluid were treated with anti–vascular endothelial growth factor monotherapy using a modified as-needed treatment algorithm. Results: Thirty-three eyes of 27 patients were included. The median age was 82 years (range, 62–94), and the median duration of follow-up was 65 months (range, 6–165). Fourteen eyes (58%) without fovea-involving fluid at baseline subsequently developed exudation after a median observation period of 16 months (range, 4–107). Ten of 24 eyes (42%) without initial macular fluid remained dry during the entire follow-up. The median number of injections required until complete fluid reabsorption was 3 (range, 1–21) during the first treatment cycle. The median time to fluid recurrence was 6 months (range, 3–74). Conclusion: Peripapillary choroidal neovascularization secondary to wet age-related macular degeneration has a slow progression, may not require treatment for a prolonged period, and responds rapidly to anti–vascular endothelial growth factor treatment with good visual outcomes. Abstract : Peripapillary choroidal neovascularization secondary to age-related macular degeneration may not require treatment in some cases, and the visual acuity may remain stable during the course of the disease.